DIFFERENTIALLY EXPRESSED GENES (DEGS) PADA Dryobalanops aromatica YANG DITUMBUHKAN PADA MEDIA GAMBUT DAN TANAH MINERAL - Yosie Syadza Kusuma; Fifi Gus Dwiyanti; Deden Derajat Matra; Ulfah Juniarti Siregar; Iskandar Zulkarnaen Siregar (Jurnal Pemuliaan Tanaman Hutan, 2021)
Dryobalanops aromatica is a highly economic value resin-producing tree and has been known as an important international trade commodity that is widely used in the perfume, cosmetic, medicine, and wood industries. In natural habitats, this species has been found to grow well on peatland and mineral soils. The information regarding adaptive genes in Indonesian native trees to abiotic stress is still very limited. The research was conducted to analyse the differentially expressed genes (DGEs) that can elucidate the role of several upregulated and down-regulated genes under peat media and mineral soil treatments. DGE analysis was carried out using R software, Bioconductor package 'edgeR'. Using the Benjamini and Hochberg approach to control FDR (FDR 0.05), with a Log2FC 2 and p-value of 0.05, showed 320 contigs were up-regulated and 439 contigs were down-regulated, while 58129 contigs were not significantly expressed. Furthermore, this study also presents an overview of the genes involved in different pathways, such as photosynthesis, carbon and energy metabolism, hormone-related genes, nitrogen metabolism, reactive oxygen species, and transcription factor. This information will be useful in understanding D. aromatica molecular responses to stress condition that may be of use for selecting genotypes in the breeding programs or peatlands restoration